1999
DOI: 10.1038/sj.bjc.6690174
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanism of daunorubicin-induced cell death in both sensitive and MDR-resistant HL-60 cells

Abstract: Summary Exposure of some acute myeloid leukaemia (AML) cells to daunorubicin leads to rapid cell death, whereas other AML cells show natural drug resistance. This has been attributed to expression of functional P-glycoprotein resulting in reduced drug accumulation. However, it has also been proposed that P-glycoprotein-expressing multidrug-resistant (MDR) cells are inherently defective for apoptosis. To distinguish between these different possibilities, we have compared the cell death process in a human AML ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…These findings are in keeping with other emerging reports linking the survival of acute myeloid leukemia cells after treatment with daunorubicin with delayed apoptosis and the formation of large endopolyploid cells (Come et al, 1999). The formation of endopolyploid cells as a response to genotoxic insult is clearly a common phenomenon of tumour cells in vitro and there are many reports linking the presence of endopolyploid tumour cells with poor response to therapy (for reviews, see Levine, 1999;Evans and Podratz, 1996).…”
Section: Discussionsupporting
confidence: 73%
“…These findings are in keeping with other emerging reports linking the survival of acute myeloid leukemia cells after treatment with daunorubicin with delayed apoptosis and the formation of large endopolyploid cells (Come et al, 1999). The formation of endopolyploid cells as a response to genotoxic insult is clearly a common phenomenon of tumour cells in vitro and there are many reports linking the presence of endopolyploid tumour cells with poor response to therapy (for reviews, see Levine, 1999;Evans and Podratz, 1996).…”
Section: Discussionsupporting
confidence: 73%
“…p53 mutant tumour cells that have incurred genotoxic stress and became tetraploid can continue endoreplication and achieve DNA content up to 8C-64C Chu et al, 2004). Association of genotoxic resistance with the induced endopolyploidy was found in rodent and human tumours (Baroja et al, 1998;Come et al, 1999). Our earlier observations revealed that transient endopolyploid p53-Burkitt lymphoma cells were able to facilitate DNA repair and release para-diploid mitotic progeny postirradiation Erenpreisa et al, 2000;Ivanov et al, 2003).…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, it has been shown that doxorubicin (anthracycline drug similar to daunorubicin) decreased apoptosis in ATRAtreated APL cells and Bfl-1/A-1 may be responsible, at least in part, for this effect [25]. Interestingly, daunorubicin is thought to trigger both apoptotic and survival pathways in the treated cells [41,42]. Anticancer agents and differentiation inducers may then have different or complementary effects on survival of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%